Compendium of bean diseases - Hall, Robert, ed. (St.Paul Minnesota The American Phytopathological Society, 1991)
Contents: Introduction -- Part I. Infectious diseases -- Part II. Noninfectious diseases -- Part III. Seed quality -- Glossary
Keywords: HABAS; PLAGAS DE PLANTAS; ENFERMEDADES DE LAS PLANTAS